Adaptation of Pseudomonas aeruginosa to Phage PaP1 Predation via O-Antigen Polymerase Mutation - Li, Gang; Shen, Mengyu; Yang, Yuhui; Le, Shuai; Li, Ming; Wang, Jing; Zhao, Yan; Tan, Yinling; Hu, Fuquan; Lu, Shuguang (Frontiers in Microbiology, 2018)
Adaptation of bacteria to phage predation poses a major obstacle for phage therapy. Bacteria adopt multiple mechanisms, such as inhibition of phage adsorption and CRISPR/Cas systems, to resist phage infection. Here, a phage-resistant mutant of Pseudomonas aeruginosa strain PA1 under the infection of lytic phage PaP1 was selected for further study. The PaP1-resistant variant, termed PA1RG, showed decreased adsorption to PaP1 and was devoid of long chain O-antigen on its cell envelope. Whole genome sequencing and comparative analysis revealed a single nucleotide mutation in the gene PA1S_08510, which encodes the O-antigen polymerase Wzy that is involved in lipopolysaccharide (LPS) biosynthesis. PA1_Wzy was classified into the O6 serotype based on sequence homology analysis and adopts a transmembrane topology similar to that seem with P. aeruginosa strain PAO1. Complementation of gene wzy in trans enabled the mutant PA1RG to produce the normal LPS pattern with long chain O-antigen and restored the susceptibility of PA1RG to phage PaP1 infection. While wzy mutation did not affect bacterial growth, mutant PA1RG exhibited decreased biofilm production, suggesting a fitness cost of PA1 associated with resistance of phage PaP1 predation. This study uncovered the mechanism responsible for PA1RG resistance to phage PaP1 via wzy mutation and revealed the role of phages in regulating bacterial behavior.